From fire suppression to fire management: Advances and resistances to changes in fire policy in the savannas of Brazil and Venezuela. Issue 1 (10th April 2018) - Eloy, Ludivine; A. Bilbao, Bibiana; Mistry, Jayalaxshmi; Schmidt, Isabel B.
Abstract : Anthropogenic fire has long shaped landscapes and livelihoods in South American savanna environments. With the growing recognition of the failures of fire suppression policies and the relevance of local peoples' practices, the Brazilian and Venezuelan governments have begun to shift to fire management policies in savanna ecosystems. Using case studies from protected areas in Cerrado and Gran Sabana, and results from two multi‐stakeholder meetings held in Parupa (Venezuela) and Brasilia (Brazil), we identify advances, resistances and challenges to inter‐cultural fire management in both countries. We show that the two regions host pioneer experiences in collaborative research based on improved dialogue and knowledge exchanges between scientists, institutions, Indigenous and local communities as well as fire management implementation including "controlled" and "prescribed" burnings. However, in some places, narrow understanding of the complexity and historical dynamics of local fire practices and the strong resistance to recognise the value of traditional fire knowledge might restrain effective participation of local communities. We argue that more collaborative research is necessary to support community owned solutions for intercultural and participative fire management in changing environmental and socio‐cultural contexts.